Pharmaceutical industry exposure in our hospitals: the final frontier. Issue 1 (18th January 2016) - Dean, Jessica; Loh, Erwin; Coleman, Justin J
Summary: Despite recent changes in attitudes, most hospitals continue to experience pharmaceutical industry presence. Pharmaceutical industry presence may be necessary and beneficial in the context of sponsorship of clinical trials with appropriate governance. Doctors continue to hold positive attitudes towards market‐oriented activities of the pharmaceutical and medical device industries. Despite evidence to the contrary, doctors believe they are able to effectively manage pharmaceutical sales representative interactions such that their own prescribing is not adversely impacted. Doctors also share a belief that small gifts and benefits are harmless. There may be significant financial burden associated with divestment of such sponsorship by hospitals. Change requires education and effective policies to manage pharmaceutical industry relationships and conflicts of interest. We discuss case studies involving students and public hospital doctors to show that divestment is possible without significant financial detriment. Health services need to be proactive in transitioning financial and cultural reliance on pharmaceutical industry sponsorship to other potentially less harmful sources.